Autonomy and respect among the postnatal mothers during maternity care in a tertiary level hospital in Nepal - Adhikari, Shila; Bajracharya, Kiran (Journal of Karnali Academy of Health Sciences, 2024)
Background: Ensuring high level of respectful maternity care encourages the women to utilize facility-based care, which is essential for improving maternal and neonatal health. Thus, the objective of the study was to find out the level of autonomy and respect during maternity care among the postnatal mothers in a tertiary level hospital in Nepal.Methods: A descriptive cross-sectional study was conducted among postnatal mothers receiving child birth services from the Tribhuvan University Teaching Hospital, Kathmandu. Two hundred and fourteen participants were selected using convenient sampling technique and interviewed using structured questionnaire in September 2018. Results: The study results indicated that 74.8% of the respondents scored above 50% in the self-reported scale of autonomy and 71% of the respondents scored above 50% in the self-reported scale of respect. A significant association was present between autonomy of postnatal mothers with caste (lower level of autonomy in those belonging to the Dalit and Disadvantaged Janajati group, p=0.005) and parity (lower level of autonomy in multipara, p=0.001). A significant association was also present between level of respect of postnatal mothers with type of delivery (lower level of respect to women having vaginal delivery, p=0.027).Conclusion: The findings revealed that one fourth of the participants had scores of less than fifty percent regarding overall autonomy and respect during maternity care. Therefore, it is recommended that doctors, nurses and supporting staff in the hospital should be provided with continuous professional development programs facilitating respectful and autonomous care.